2007
DOI: 10.1021/la700729q
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) Gradient for Biochip Development

Abstract: A novel method of producing a poly(ethylene glycol) (PEG)-based gradient matrix that varies gradually in thickness from 0 to 500 A over a distance of 5-20 mm is presented. The gradient matrix is graft copolymerized from a mixture of PEG methacrylates onto organic thin films providing free radical polymerization sites initiated by UV irradiation at 254 nm. The films used as grafting platforms consist of either a spin-coated cycloolefin polymer or a self-assembled monolayer on planar gold. The thickness/irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 42 publications
3
58
1
Order By: Relevance
“…In order to determine the minimum thickness required, the patterning technique was combined with a method that enables fabrication of hydrogel thickness gradients. This approach has been used previously to investigate protein immobilization and biomolecular interactions within related hydrogels 29, 32. The patterned hydrogel was prepared on a PS film spin‐coated on a silanized silicon wafer to simulate the use of a plastic substrate yet enabling reliable thickness measurements with ellipsometry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to determine the minimum thickness required, the patterning technique was combined with a method that enables fabrication of hydrogel thickness gradients. This approach has been used previously to investigate protein immobilization and biomolecular interactions within related hydrogels 29, 32. The patterned hydrogel was prepared on a PS film spin‐coated on a silanized silicon wafer to simulate the use of a plastic substrate yet enabling reliable thickness measurements with ellipsometry.…”
Section: Resultsmentioning
confidence: 99%
“…The immobilized proteins appear to have retained their biological activity and were clearly accessible for cellular interactions. In previous works, we have noted that the poly(PEG 10 MA‐ co ‐HEMA) hydrogel constitutes a significant barrier to protein diffusion, particularly for larger proteins 29, 32. This may be a disadvantage if the intended use for the hydrogel is as a 3D matrix for the study of protein–protein interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have witnessed explosive growth of interest in motion and transportation of liquid droplet on solid surface for its significant application in micro/nano-fluidic devices [1][2][3][4][5][6], condensation heat transfer [7], cell motility [8][9][10] and biochips [11][12][13][14][15]. Therefore, in order to manipulate the motion of liquid droplet in these application fields, many approaches have been proposed such as applying electric field [16,17], external force [18] or implementing a gradient [19][20][21][22] (e.g., wetting gradient and thermal gradient [23]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that PEGMA:HEMA polymer brushes can be grafted on air plasma‐treated cycloolefin‐polymer‐coated substrates using SIPGP 18. For example, Larsson et al also prepared PEG hydrogel micropatterns and gradients on different thiol and silane self‐assembled monolayers (SAMs) 10, 19. So far the smallest features made by illuminating the sample and monomer solution through a photomask are 5 μm‐wide lines 10…”
mentioning
confidence: 99%